Neocortical-hippocampal dynamics of working memory in healthy and diseased brain states based on functional connectivity - Campo, Pablo; Poch, Claudia (Frontiers in Human Neuroscience, 2012)
Working memory is the ability to transiently maintain and manipulate internal representations beyond its external availability to the senses. This process is thought to support high level cognitive abilities and been shown to be strongly predictive of individual intelligence and reasoning abilities. While early models of working memory have relied on a modular perspective of brain functioning, more recent evidence suggests that cognitive functions emerge from the interactions of multiple brain regions to generate large-scale networks. Here we will review the current research on functional connectivity of working memory processes to highlight the critical role played by neural interactions in healthy and pathological brain states. Recent findings demonstrate that working memory abilities are not determined solely by local brain activity, but also rely on the functional coupling of neocortical-hippocampal regions to support working memory processes. Although the hippocampus has long been held to be important for long-term declarative memory, recent evidence suggests that the hippocampus may also be necessary to coordinate disparate cortical regions supporting the periodic reactivation of internal representations in working memory. Furthermore, recent brain imaging studies using connectivity measures, have shown that changes in cortico-limbic interactions can be useful to characterize working memory impairments observed in different neuropathological conditions. Recent advances in electrophysiological and neuroimaging techniques to model network activity has led to important insights into how neocortical and hippocampal regions support working memory processes and how disruptions along this network can lead to the memory impairments commonly reported in many neuropathological populations.